2017
DOI: 10.1097/inf.0000000000001563
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF on Stool Is Useful for the Rapid Diagnosis of Tuberculosis in Young Children With Severe Pulmonary Disease

Abstract: Background Tuberculosis (TB) continues to result in high morbidity and mortality in children from resource-limited settings. Diagnostic challenges, including resource-intense sputum collection methods and insensitive diagnostic tests, contribute to diagnostic delay and poor outcomes in children. We evaluated the diagnostic utility of stool Xpert MTB/RIF (Xpert) compared with bacteriologic confirmation (combination of Xpert and culture of respiratory samples). Methods In a hospital-based study in Cape Town, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 33 publications
5
54
0
5
Order By: Relevance
“…Culture identification also has limited role in routine diagnosis in India and is recommended for screening of drug-resistance 5,6 . Many recent studies have tested efficacy of stool in molecular diagnosis of pediatric PTB, while scarce reports are available on adult stool testing for detection of PTB from other countries [7][8][9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…Culture identification also has limited role in routine diagnosis in India and is recommended for screening of drug-resistance 5,6 . Many recent studies have tested efficacy of stool in molecular diagnosis of pediatric PTB, while scarce reports are available on adult stool testing for detection of PTB from other countries [7][8][9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…Out of 440 records screened, 30 studies (31 articles)5–35 were included in the review (online Supplementary figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Other non-respiratory specimens have been tested using Xpert MTB/RIF in children. Previous studies have shown that stool Xpert has similar performance as gastric aspirate in HIVinfected children (LaCourse et al, 2018) and in those with severe pulmonary disease (Walters et al, 2017), however, processing of stool samples is tedious and may not be readily done in peripheral laboratories.…”
Section: Discussionmentioning
confidence: 99%